2014
DOI: 10.4265/bio.19.11
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Heavily Oil-Polluted Seawater by a Bacterial Consortium Immobilized in Cocopeat and Rice Hull Powder

Abstract: We examined the effectiveness of cocopeat and rice hull powder obtained from agricultural wastes as biocarriers for an oil-degrading bacterial consortium. Scanning electron microscopy revealed colonization and strong attachment of bacterial cells on the surface of both carriers. Results of a 60-day in vitro seawater bioremediation trial showed significant oil reduction and high cultivable bacterial counts in treatments augmented with the carrier-attached bacterial consortia compared to treatments supplemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Xu and Lu [29] demonstrated that oil removal in a crude-oil-contaminated soil was increased by application of hydrocarbon-degrading bacteria immobilized on peanut hull powder as the biocarrier. The oil-degrading ability of the immobilized bacterial consortium in cocopeat, rice hull powder and sodium alginate capsules was compared by Nunal et al [30].…”
Section: Crude Oil Degradation By Free and Cryogel Immobilized Bactermentioning
confidence: 99%
“…Xu and Lu [29] demonstrated that oil removal in a crude-oil-contaminated soil was increased by application of hydrocarbon-degrading bacteria immobilized on peanut hull powder as the biocarrier. The oil-degrading ability of the immobilized bacterial consortium in cocopeat, rice hull powder and sodium alginate capsules was compared by Nunal et al [30].…”
Section: Crude Oil Degradation By Free and Cryogel Immobilized Bactermentioning
confidence: 99%
“…According to Alesandrello et al (2017), a mixture biofilm of Pseudomonas monteilii P26 and Gordonia sp. H19 attached on polyurethane foam could remove 75% of petroleum oil with the initial concentration of 0.1 g per 100 mL medium after 7 dayincubation at 30 o C. Nunal et al (2014) demonstrated that a biofilm of bacterial consortium formed on cocopeat and rice husk powder significantly degraded both aliphatic and aromatic fractions after 60-day in vitro experiments. These results showed the effectiveness of biofilm adherence on several kinds of biocarriers and in agreement with our obtained results.…”
Section: Total Petroleum Hydrocarbons Analysismentioning
confidence: 96%
“…The results provided in Table 4 indicated that the sample 6 including 1 g of the product with 100 g contaminated sediment has the better degradation capacity in comparison with biofilm from single species (sample 1 to sample 4) or mixture biofilm of 4 strains without carrier (sample 5) or the carrier without bacteria (sample 7) or the control without neither biocarrier nor bacteria. Bacteria formed biofilm on carriers improved the survival and retention of biodegradation factors in oil contaminated areas (Nunal et al, 2014). The attachment enhanced the aromatic and aliphatic hydrocarbon degradation (Alesandrello et al, 2017).…”
Section: Aromatic Hydrocarbons Degradationmentioning
confidence: 99%
“…Nuñal et al, [23] suggested that the obtained bacterial counts may be lower than the actual counts as strongly adsorbed bacteria may be difficult to dislodge. Nuñal et al, [23] had reported cell viability after storage of rice hull and cocopeat-immobilized bacterial consortia at temperatures of-30°C, 0°C and room temperatures after six months. This result suggests that immobilized cells can be stored without losing their metabolic activities.…”
Section: Scanning Electron Microscopic Images Of Melon Husk Without the Consortium (A) Withmentioning
confidence: 99%